ANALYSIS OF FACTORS AFFECTING DOMESTIC INVESTMENT IN NORTH SUMATRA PROVINCE - Reza Juanda; Indah Mardianti (Journal of Malikussaleh Public Economics, 2022)
This study examined the effect of inflation, exchange rates, and interest rates on domestic investment in the province of North Sumatra for the 2010-2020 period. This study used the Multiple Linear Regression method. The results partially indicated that inflation negatively and insignificantly influenced domestic investment, the exchange rate positively but insignificantly influenced domestic investment, and the interest rate negatively and insignificantly influenced domestic investment in Indonesia. North Sumatra Province. Simultaneously, inflation, exchange rate, and interest rate positively and significantly influenced domestic investment in North Sumatra.